Value of teff (Eragrostis tef) genetic resources to support breeding for conventional and smallholder farming: a review - Aemiro Bezabih Woldeyohannes; Ermias Abate Desta; Carlo Fadda; Mario Enrico Pè; Matteo Dell’Acqua (CABI Agriculture and Bioscience)
Abstract Crop germplasm collections are a key asset to support the resilience and productivity of cropping systems worldwide. In their diversity lays an oftentimes untapped reservoir of alleles that may enable breeding strategies targeting local adaptation, resulting in enhanced performance and higher varietal uptake. In the past five decades, the national genebank of Ethiopia actively collected and conserved thousands of teff (Eragrostis tef) accessions, a staple crop throughout the Horn of Africa at the basis of countless cultural uses and with high market relevance. This review article emphasizes the breeding significance of teff genetic resources, highlighting current challenges in teff farming and improvement that could be addressed further valorising germplasm collections. We collect data generated on the largest teff ex situ collections in the world to discuss opportunities to improve teff tolerance to stress and lodging, as well as to increase its productivity across its cropping area. In doing so, we highlight and critically revise current and past literature tapping in teff diversity to support teff improvement. This review starts providing a summary of teff characteristics, detailing the status and challenges of teff cultivation and breeding. It then follows describing the diversity existing in teff diversity collections and its relevance for teff improvement. The review concludes describing the molecular studies undertook on teff in the past two decades, highlighting the perspectives of molecular breeding for teff. The body of knowledge available on teff shows that there is large potential for improvement of this crop to target smallholder farming systems as well as international markets, and that improvement may start from the large diversity available in teff collections.